2017
DOI: 10.1158/0008-5472.can-16-2170
|View full text |Cite
|
Sign up to set email alerts
|

ESE3 Inhibits Pancreatic Cancer Metastasis by Upregulating E-Cadherin

Abstract: The ETS family transcription factor ESE3 is a crucial element in differentiation and development programs for many epithelial tissues. Here we report its role as a tumor suppressor in pancreatic cancer. We observed drastically lower ESE3 expression in pancreatic ductal adenocarcinomas (PDAC) compared to adjacent normal pancreatic tissue. Reduced expression of ESE3 in PDAC correlated closely with an increase in lymph node metastasis and vessel invasion and a decrease in relapse-free and overall survival in pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…Our previously data demonstrated tumoral ESE3 inhibits PDAC EMT and metastasis by transcriptionally up-regulating E-cadherin (Zhao et al, 2017) . Interestingly, although ESE3 expression was down-regulated in PDAC cells, we observed robust upregulation of ESE3 in PSC in PDAC tissues when compared to normal pancreatic tissue ( Fig.…”
Section: Ese3 Was Overexpressed In Activated Pscmentioning
confidence: 85%
See 1 more Smart Citation
“…Our previously data demonstrated tumoral ESE3 inhibits PDAC EMT and metastasis by transcriptionally up-regulating E-cadherin (Zhao et al, 2017) . Interestingly, although ESE3 expression was down-regulated in PDAC cells, we observed robust upregulation of ESE3 in PSC in PDAC tissues when compared to normal pancreatic tissue ( Fig.…”
Section: Ese3 Was Overexpressed In Activated Pscmentioning
confidence: 85%
“…In pancreatic cancer, our previous investigation identified ESE3 as a tumor suppressor. ESE3 overexpression in tumor cells transcriptionally up-regulates E-cadherin to prevent EMT and metastasis (Zhao et al, 2017) . Moreover, ESE3 overexpression in PDAC cells down-regulates TGFβ1 and GM-CSF (Liu et al, 2019) to inhibit Treg induction and MDSC accumulation, which in turn increase sensitivity to immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…E-cadherin is a key factor in cell-cell adhesion. The destruction of E-cadherin is thought to be one of the first steps in metastasis, playing critical roles in tumor metastasis [21,[31][32][33]. Recent reports have shown that a decrease in E-cadherin is strongly associated with metastasis and poor clinical prognosis and suggested that targeting E-cadherin could be a promising therapeutic approach for metastatic CRC [34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated whether Peer-reviewed version available at Cancers 2019, 11, 942; doi:10.3390/cancers11070942 of a tool to circumvent the pro-tumour M2 addicted immune suppressive-environment [44]. Secondly, due to the differential E-cadherin expression, PANC-1 can be controlled in their invasive phenotype [45]. Conversely, the absence of E-cadherin modulation might contribute to the MIAPaCa-2 relative decreased sensitivity to XAV-939.…”
Section: Discussionmentioning
confidence: 99%